Uncovering the Potential of Biomass from Agricultural Waste as Sustainable Biofuel in Aviation Industry to Promote Net Zero Emissions: A Critical Review - Tonni Agustiono Kurniawan (BioResources)
It is hard to decarbonize a passenger jet. The aviation industry contributes to approximately 2.5% of global greenhouse gas emissions, underscoring the need for decarbonization to achieve net-zero emissions by 2050. Sustainable aviation fuels (SAFs) derived from conventional biomass, i.e., agricultural residues, forestry by-products, and organic waste, present a scalable solution. Conventional biomass has the potential to produce 60 to 80 billion liters of SAF annually, meeting up to 20% of current jet fuel demand. Lifecycle assessments indicate GHG emission reductions of 70 to 85% compared to fossil fuels. Advanced conversion technologies such as gasification and fermentation have achieved efficiencies exceeding 65%, demonstrating commercial viability. Case studies highlight significant CO2 reductions of 50 to 70% per flight using SAFs. Despite its promise, biomass-based SAFs are costlier, ranging from USD 1.10 to USD 2.40 per liter. However, policy instruments such as the U.S. SAF Grand Challenge and the EU’s RED II are accelerating adoption. Beyond environmental benefits, SAFs support socio-economic development, potentially creating 1.2 million green jobs globally while addressing waste management challenges. To realize this potential, challenges in technology, economics, and policy need to be addressed. Coordinated efforts in policy, research, and investment are essential to scale SAF deployment, enabling the aviation sector to significantly reduce lifecycle emissions and achieve its net-zero ambitions.